2011
DOI: 10.3892/mmr.2011.490
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal essential fatty acid deficiency in mice results in long-term gender-specific effects on body weight and glucose metabolism

Abstract: Abstract. Essential fatty acids are important for normal growth and development in early life. However, the long-term effects of prenatal essential fatty acid deficiency (EFAD) on the adult metabolism remain to be determined. The aim of this study was to investigate the effects of an EFAD diet given to mice during late gestation on body weight and body composition, and metabolism in the adult offspring. Pregnant dams were given an EFAD or a control diet during the last 10 days of gestation. After delivery, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To test our hypothesis, the offspring of two rodent species, C57Bl/6j mice and Wistar rats, were used; both of which are commonly used models to study metabolic programming [16,17,18,19,20]. The experimental design, intended to expose offspring to increased MCFA levels during lactation and early post-weaning, would enable us to selectively investigate the importance of early dietary FA composition during a critical period for WAT development [21].…”
Section: Methodsmentioning
confidence: 99%
“…To test our hypothesis, the offspring of two rodent species, C57Bl/6j mice and Wistar rats, were used; both of which are commonly used models to study metabolic programming [16,17,18,19,20]. The experimental design, intended to expose offspring to increased MCFA levels during lactation and early post-weaning, would enable us to selectively investigate the importance of early dietary FA composition during a critical period for WAT development [21].…”
Section: Methodsmentioning
confidence: 99%
“…The reduced birth weight and the lower body weight gain during development were a characteristic effect of EFAD [19] [20]. To reduce body weight, there is evidence that EFAD leads to increased basal metabolism [21] [22], although its actual mechanism is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, given the EFA deficient/high saturated fat diet only during second half of pregnancy, the birth weight of the offspring was lower than in the control group and remained so in the female offspring to adulthood at 15 weeks of age . The dams were switched to ordinary chow at delivery, so the offspring was mainly raised on milk from normally fed dams and continued ordinary chow after weaning.…”
Section: Experiments With Diets Deficient In Efa/rich In Saturated Famentioning
confidence: 97%
“…Intraperitoneal glucose tolerance test (IPGTT) at 12 weeks of age showed that both gender had a similar glucose tolerance as controls but the male offspring from the experimental group had higher fasting insulin and glucose and a significantly higher insulin production up to 60 min after injection, while the females had a completely congruent insulin curve to that of the controls . The study has limitations since the pups were influenced by the dam's changed metabolism at the start of the lactation period and were not followed as long as the animals in the other studies, making comparisons difficult.…”
Section: Experiments With Diets Deficient In Efa/rich In Saturated Famentioning
confidence: 99%